Conceição Evaristo: do imaginário racial à circularidade de seu dizer - Albuquerque, Karla Daniel Martins de Souza (2021)
This study, based on the theoretical/methodological assumptions of Discourse Analysis, from a French line, derived from Michel Pêcheux (1975), seeks to listen to the discursive functioning of the voice of the writer Conceição Evaristo, which pervades a discursive memory that runs through colonial times to the present days. We analyzed the displacement of meanings around the racial complexities materialized by the positions that Conceição Evaristo assumes in the enunciation through interviews. Therefore, our corpus consists of clippings from two selected interviews. The first is found in “Nexo Jornal” (2017), entitled “Conceição Evaristo:‘ my writing is contaminated by the black women condition’”. The second, on the website “Brasil de fato” (2018), entitled “Conceição Evaristo: ‘Don’t just read my biography. Read my texts’". In them, according to her subject positions, when enunciating as a woman, black woman, writer, professor, philosopher, she discusses the militancy and the silencing of black authors and - focus of our research - also of black writers who, even under controversial conditions regarding the delegitimization of their writings, in the positions of writers, philosophers, thinkers, have been building conditions of resistance in their insistence on writing. In this political act, we have an event in history marked by registries (escrevivência according to the author), a counter-speech in which socially neglected voices by black women are no longer silenced; they are placed and heard by the reading subjects. With this, our objective is to analyze the repercussions of the saying elaborated by Conceição Evaristo's subject positions when discussing, through imaginary formations and memory, the notions of race, class and gender, which is structuring of/in social relations. In this sense, we also reflected on the insertion and path of the discourse repeated by Conceição Evaristo, materialized in the interviews. Finally, we propose a reading that seeks to understand how Conceição Evaristo sustains, in her subject positions of woman, black woman, professor, writer, a basic representative saying for resisting the socially dominant collective imagination.